Novel pyrrolopyrimidines as Mps1/TTK kinase inhibitors for breast cancer. Issue 7 (1st April 2017) - Sugimoto, Yasuro; Sawant, Dwitiya B.; Fisk, Harold A.; Mao, Liguang; Li, Chenglong; Chettiar, Somsundaram; Li, Pui-Kai; Darby, Michael V.; Brueggemeier, Robert W.
Graphical abstract: Abstract: New targeted therapy approaches for certain subtypes of breast cancer, such as triple-negative breast cancers and other aggressive phenotypes, are desired. High levels of the mitotic checkpoint kinase Mps1/TTK have correlated with high histologic grade in breast cancer, suggesting a potential new therapeutic target for aggressive breast cancers (BC). Novel small molecules targeting Mps1 were designed by computer assisted docking analyses, and several candidate compounds were synthesized. These compounds were evaluated in anti-proliferative assays of a panel of 15 breast cancer cell lines and further examined for their ability to inhibit a variety of Mps1-dependent biological functions. The results indicate that the lead compounds have strong anti-proliferative potential through Mps1/TTK inhibition in both basal and luminal BC cell lines, exhibiting IC50 values ranging from 0.05 to 1.0 μM. In addition, the lead compounds1 and13 inhibit Mps1 kinase enzymatic activity with IC50 values from 0.356 μM to 0.809 μM, and inhibited Mps1-associated cellular functions such as centrosome duplication and the spindle checkpoint in triple negative breast cancer cells. The most promising analog, compound13, significantly decreased tumor growth in nude mice containing Cal-51 triple negative breast cancer cell xenografts. Using drug discovery technologies, computational modeling, medicinal chemistry, cell culture and in vivo assays, novel small molecule Mps1/TTK inhibitors have been identified as potential targeted therapies for breast cancers.